The effect of chiling temperatures on soybean seedlings - Chifunda, Ethel Chitimbwa (My University, 2018)
Soybean is an economically important crop in South Africa and the South African Bureau for food and agricultural policy projected an increase in land assigned for commercial soybean. Environmental stresses can affect aspects of plant growth and development, consequently specific morphology, anatomically and physiological parameters. In this regard, the present study determined the responses of soybean seedlings to chilling stress. Results were a tool for evaluation of sensitivity of soybean seedlings to chilling stress. Experiments were carried out to assess the possible effects of chilling temperatures (5°C and 15°C) with respect to control (25°C) on soybean leaves at seedling stage for 24 and 72 hours. The following were analysed- Leaf functional parameters (leaf vigour, shape, colour); Physical parameters dry weight (DW), fresh weight (FW) and relative water content (RWC); Microscopic analysis and Reactive Oxygen Species (ROS) investigation by assessing superoxide concentrations. Full turgidity in leaves was evident in the control, leaf curling was observed at 15°C and wilting leaves were observed at 5°C temperature treatment. As samples were exposed to 5°C temperatures, FW and RWC declined during extended periods of exposure. Effects on growth indexes were observed as early as 24 hours. A significant decrease in RWC was observed between 15°C and 5°C with 9%±2 and 13%±2 respectively. When compared to the control, significant decrease occurred in the palisade mesophyll layer at 15°C (12±2μm) and adaxial layer at 5°C (12±2μm). This suggests that the upper epidermis was possibly the most affected part of the leaf and cell modification could have occurred. Changes in DW, leaf thickness, spongy mesophyll layer, abaxial layer and superoxide accumulation were not statistically significant and were not affected by chilling temperature stress. TEM studies illustrated changes in chloroplasts profiles, formation of vesicles, disappearance of starch grains, incipient plasmolysis could indicate that the low temperature treatments resulted in stresses which lead to more production of ROS and subsequently cellular damage, which was more pronounced on 5°C treatment. Therefore, environmental stresses can affect aspects of plant growth and development. Our study illustrated that a decrease in RWC, curling of leaves and wilting of leaves as well as growth of microorganisms especially fungi are effects of chilling temperatures on soybean seedling leaves. It is important to determine how soybean phenology is influenced by short term chilling temperatures as these changes are directly associated with anatomical, morphological, physiological changes. This gives us information on developmental changes that can be used for predicting soybean phenology under field conditions where short term exposure to chilling temperatures is likely to occur during seedling development.
A research project submitted to the Faculty of Science, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Masters of Science in Environmental Science Coursework and Research Report Signed on the 10th of August 2018 in Johannesburg
Keywords: Soybean--Breeding--South Africa; Soybean--Genetics; Species diversity